Evaluating discrete choice experiment willingness to pay [DCE-WTP] analysis and relative social willingness to pay [RS-WTP] analysis in a health technology assessment of a treatment for an ultra-rare childhood disease [CLN2]. (19th May 2022) - Moro, Domenico; Schlander, Michael; Telser, Harry; Sola-Morales, Oriol; Clark, Michael David; Olaye, Andrew; Camp, Charlotte; Jain, Mohit; Butt, Thomas; Bakshi, Sumeet
ABSTRACT: Background: Conventional cost-effectiveness analysis [CEA] using cost per QALY thresholds may counteract other incentives introduced to foster development of treatments for rare and ultra-rare diseases. Therefore, alternative economic evaluation methods were explored, namely Discrete Choice Experiment Willingness to Pay (DCE-WTP) and Relative Social Willingness to Pay (RS-WTP), to value interventions for an ultra-rare childhood disease, Neuronal Ceroid Lipofuscinosis type 2 (CLN2). Research Design and Methods: Treatment for CLN2 was valued from a citizen's ('social') perspective using DCE-WTP and RS-WTP in a survey of 4, 009 United Kingdom [UK] adults. Three attributes (initial quality of life, treatment effect, and life expectancy) were used in both analyses. For DCE-WTP, a cost attribute (marginal income tax increase) was also included. Optimal econometric models were identified. Results: DCE-WTP indicated that UK adults are willing to pay incremental increases through taxation for improvements in CLN2 attributes. RS-WTP identified a willingness to allocate >40% of a pre-assigned healthcare budget to prevent child mortality and approximately 15% for improved health status. Conclusions: Both techniques illustrate substantive social WTP for CLN2 interventions, despite the small number of children benefitting. This highlights a gap between UK citizens' willingness to spend on rare disease interventions and current funding policies.